Advances in Unmanned Aerial Vehicle-Based Sensing and Imaging - Marios Antonakakis; Michail Zervakis (Sensors)
Unmanned Aerial Vehicle (UAV)-based sensing and imaging represent a cutting-edge approach to addressing the critical need for the real-time, accurate, and automated data collection and analysis of physical events on Earth’s surface [...]